Pemodelan banjir pluvial perkotaan berbasis SWMM untuk strategi mitigasi di kawasan Ciledug seskoal, Jakarta Selatan - Chandra dewi; Dian Krisnawati; Airu Nahdloh; Dian Candra Rini Novitasari (Papanda Publisher, 2026)
Urban pluvial flooding is one of the most frequent hydrometeorological disasters in densely populated areas and is a serious problem for many cities around the world. This flooding is triggered by high rainfall intensity, represented by the Intensity Duration Frequency (IDF) curve, as well as limited drainage network capacity due to inadequate channel size, hydraulic roughness, sedimentation, and waste accumulation. To address these issues, this study applies an integrated modeling method between SWMM and a 2D hydrodynamic model using rainfall data derived from Intensity Duration Frequency (IDF) analysis based on historical rainfall records from BMKG during the period 2014-2024, DEM/topography, land use, drainage channel characteristics, and actual inundation observations in the Ciledug Seskoal area, South Jakarta. This study aims to analyze the characteristics of pluvial flooding in the study area and evaluate the performance of the SWMM–2D model in simulating surface runoff and flooding processes. The calibration results show that the model is able to capture inflow patterns and hydrographs that are consistent with the observation data. Model validation demonstrated moderate agreement between simulated and observed inundation depths, with a correlation coefficient of r = 0.79 (R² = 0.63). The distribution of flooding depth indicated that most of the affected areas experienced flooding of more than 60 cm, signifying a significant level of risk. The novelty of this study lies in the integration of SWMM and a 2D hydrodynamic model validated with actual inundation data in a dense urban setting, which improves the accuracy of pluvial flood simulation compared to conventional methods. Overall, the integrated SWMM-2D model proved effective in predicting urban pluvial flood characteristics and can be used as a scientific basis for formulating flood mitigation strategies in densely populated residential areas